Targeting IL13Ralpha2 activates STAT6-TP63 pathway to suppress breast cancer lung metastasis. Issue 1 (December 2015) - Papageorgis, Panagiotis; Ozturk, Sait; Lambert, Arthur; Neophytou, Christiana; Tzatsos, Alexandros; Wong, Chen; Thiagalingam, Sam; Constantinou, Andreas
Abstract Introduction Basal-like breast cancer (BLBC) is an aggressive subtype often characterized by distant metastasis, poor patient prognosis, and limited treatment options. Therefore, the discovery of alternative targets to restrain its metastatic potential is urgently needed. In this study, we aimed to identify novel genes that drive metastasis of BLBC and to elucidate the underlying mechanisms of action. Methods An unbiased approach using gene expression profiling of a BLBC progression model andin silico leveraging of pre-existing tumor transcriptomes were used to uncover metastasis-promoting genes. Lentiviral-mediated knockdown of interleukin-13 receptor alpha 2 (IL13Ralpha2) coupled with whole-body in vivo bioluminescence imaging was performed to assess its role in regulating breast cancer tumor growth and lung metastasis. Gene expression microarray analysis was followed by in vitro validation and cell migration assays to elucidate the downstream molecular pathways involved in this process. Results We found that overexpression of the decoy receptor IL13Ralpha2 is significantly enriched in basal compared with luminal primary breast tumors as well as in a subset of metastatic basal-B breast cancer cells. Importantly, breast cancer patients with high-grade tumors and increased IL13Ralpha2 levels had significantly worse prognosis for metastasis-free survival compared with patients with low expression. Depletion of IL13Ralpha2 in metastatic breast cancer cells modestly delayed primary tumor growth but dramatically suppressed lung metastasis in vivo. Furthermore, IL13Ralpha2 silencing was associated with enhanced IL-13-mediated phosphorylation of signal transducer and activator of transcription 6 (STAT6) and impaired migratory ability of metastatic breast cancer cells. Interestingly, genome-wide transcriptional analysis revealed that IL13Ralpha2 knockdown and IL-13 treatment cooperatively upregulated the metastasis suppressor tumor protein 63 (TP63) in a STAT6-dependent manner. These observations are consistent with increased metastasis-free survival of breast cancer patients with high levels ofTP63 andSTAT6 expression and suggest that the STAT6-TP63 pathway could be involved in impairing metastatic dissemination of breast cancer cells to the lungs. Conclusion Our findings indicate that IL13Ralpha2 could be used as a promising biomarker to predict patient outcome and provide a rationale for assessing the efficacy of anti-IL13Ralpha2 therapies in a subset of highly aggressive basal-like breast tumors as a strategy to prevent metastatic disease.